Pemberdayaan Masyarakat Dalam Upaya Pencegahan Stunting Di RT. 34 Kelurahan Pematang Gubernur Kota Bengkulu - Palingga, Imelda; Lestari, Neka Puji; Chandra Herlani; Rizki billy; Rosihanna; Yusran Fauzi; Tuti Rohani; Danur Azissah; Sari, Fikitri Marya (Jurnal Pengabdian Mitra Persada, 2025)
This community service activity aims to provide outreach and counseling in efforts to prevent stunting in Rt.34 kelurahan pematang gubernur kecamatan Muara Bangkahulu. Stunting is a problem because it can cause pain, death, slow down the motor development process and inhibit the mental growth process of sufferers. The targets of this counseling activity are prospective brides, pregnant women and mothers who have toddlers. Implementation of activities in collaboration with the apparatus Rt and health center Muara Bangkahulu. implemented with socialization and counseling methods. The material presented is the definition of stunting, characteristics of stunting, causes and prevention of stunting. The result of this activity is an increase in public understanding Rt about what stunting is, the characteristics of stunting, causes, prevention of stunting, and long-term dangers as well as growing awareness in dealing with the impacts of stunting so as to minimize the occurrence of stunting in infants, toddlers and children.